Microautophagy: distinct molecular mechanisms handle cargoes of many sizes - Schuck, Sebastian (Journal of cell science, 2020)
Autophagy is fundamental for cell and organismal health. Two types of autophagy are conserved in eukaryotes: macroautophagy and microautophagy. During macroautophagy, autophagosomes deliver cytoplasmic constituents to endosomes or lysosomes, whereas during microautophagy lytic organelles take up cytoplasm directly. While macroautophagy has been investigated extensively, microautophagy has received much less attention. Nonetheless, it has become clear that microautophagy has a broad range of functions in biosynthetic transport, metabolic adaptation, organelle remodeling and quality control. This Review discusses the selective and non-selective microautophagic processes known in yeast, plants and animals. Based on the molecular mechanisms for the uptake of microautophagic cargo into lytic organelles, I propose to distinguish between fission-type microautophagy, which depends on ESCRT proteins, and fusion-type microautophagy, which requires the core autophagy machinery and SNARE proteins. Many questions remain to be explored, but the functional versatility and mechanistic diversity of microautophagy are beginning to emerge.
Gesehen am 04.01.2021